When Should We Stop Breeding Dairy Cows? - Klibs N. Galvão; Albert De Vries (EDIS)
The decision of when to start and when to stop breeding cows during a lactation is often a challenging one for dairy producers. This 3-page fact sheet presents practical rules on how to determine when to stop breeding Holstein dairy cows based on persistency of milk production and break-even point for milk production. Written by Klibs N. Galvão and Albert De Vries, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, July 2014.